REVEAL THE MYSTERY OF RITUAL SESAJEN (TOHO DORE) ON MBOJO TRIBE IN BIMA - Nurnazmi Nurnazmi; Arifuddin Arifuddin; Nurhasanah Nurhasanah; Irfan Irfan; Ida Waluyati; ST Nurbayan; Syaifullah Syaifullah (Jurnal Sosiologi Reflektif, 2020)
The ritual offering of “toho dore” is a religious tradition carried out by the ancestors based on animism concept of “ma kakamba” and dynamism concept of “ma kakimbi”, which are still believed and practiced by some Mbojo tribes. The purpose of this study is to describe the meaning of ritual offerings (toho dore) for the Mbojo tribe community in Bima Regency; and to describe the ritual mystery (toho ra dore) in the Mbojo tribe of Bima Regency. The research approach uses a qualitative approach, ethnographic methods. Data collection techniques used are interviews, observations and documentations. Data analysis techniques using data reduction, data display and data verification. Testing the authenticity of the data using time triangulation, data sources and data collection techniques. All of the data are interpreted using Symbolic Interactionalism theory of George Herbert Mead. The findings show that ritual offerings serve people of Mbojo for various purposes: (1) Ritual offerings (toho dore) to obtain offspring, (2) Ritual offerings (toho dore) as a means of obtaining abundant harvests, (3) Ritual offerings (toho dore) to obtain large livestock yields, such as cattle and buffalo, (4) Ritual offerings (toho dore) to get a lot of sustenance when trading, even though the products sold are not as good and as many products as other business partners, (5) Ritual offerings (toho dore) to keep rice in the rice container (tewu bongi), (6) Ritual offerings (toho dore) so that the child in the content is not lost, (7) Ritual offerings (toho dore) to get a mate. Ritual sesajen (toho dore) merupakan suatu perilaku yang dilakukan oleh para nenek moyang atas kepercayaan pada dinamisme (ma kakamba) dan animisme (ma kakimbi) yang masih dipercayai dan dilaksanakan oleh sebagian suku Mbojo yang mempercayai keajaiban ritual-ritual tersebut. Lokasi-lokasi tertentu yang dipercayai oleh masyarakat untuk meletakkan sesajen (toho dore) yang terdiri dari kelapa muda, pisang, nasi ketan (oha mina), daun sirih, pinang dan ayam kampung yang berwarna putih atau hitam semua bulunya. Tujuan penelitian ini untuk mendeskripsikan makna ritual sesajen (toho dore) bagi masyarakat suku Mbojo di Kabupaten Bima; dan untuk mendeskripsikan misteri ritual (toho dore) di suku Mbojo Kabupaten Bima. Teori yang digunakan yakni teori interaksionalisme simbolis George Herbert Mead. Pendekatan penelitian menggunakan pendekatan kualitatif, metode etnografi. Informan utama sejumlah 11 orang dan informan pendukung 3 orang, teknik sampling yang digunakan yakni snowball sampling. Teknik pengumpulan data menggunakan teknik interview, observasi dan dokumentasi. Teknik analisis data menggunakan reduksi data, display data dan verifikasi data. Pengujian keabsahan data menggunakan triangulasi waktu, sumber data dan teknik pengumpulan data. Temuan hasil penelitian terdiri dari (1) Ritual sesajen (toho dore) untuk mendapatkan keturunan, (2) Ritual sesajen (toho dore) sebagai sarana mendapatkan hasil panen berlimpah, (3) Ritual sesajen (toho dore) untuk mendapatkan hasil ternak yang banyak, seperti sapi dan kerbau, (4) Ritual sesajen (toho dore) untuk mendapatkan rezeki yang banyak saat berdagang padahal produk yang dijual tidak sebagus dan sebanyak produk rekan bisnis lainnya, (5) Ritual sesajen (toho dore) untuk tetap memiliki beras dalam tempat beras (tewu bongi), (6) Ritual sesajen (toho dore) agar anak dalam kandungan tidak hilang, (7) Ritual sesajen (toho dore) untuk mendapatkan jodoh, (8) Ritual sesajen (toho dore) untuk menyembuhkan sakit jiwa.